Editorial: Volume 2, Issue 1 – Journal of Economics, Law and Society (JELS) (Journal of Economics, Law and Society, 2025)
It is with great pleasure that we present the first issue of the second volume of the Journal of Economics, Law and Society (JELS), published by the Economic and Social Research Institute (ESREIN). Now entering its second year of publication, JELS continues to grow in both substance and reach. We remain steadfast in our mission to provide a dynamic, interdisciplinary platform for scholarly dialogue, critical analysis, and research dissemination at the intersection of economics, law, finance, and broader social issues.Despite being a relatively young publication, JELS has made remarkable progress in building its academic presence. The journal is now indexed and abstracted in reputable platforms such as Google Scholar, CrossRef, ResearchBib, Index Copernicus, Scilit, Zenodo, and OpenAIRE. Our goal remains to further elevate the journal’s visibility and academic recognition by seeking inclusion in leading citation indices such as Scopus and the Web of Science. This commitment reflects not only our internal dedication but also the quality of submissions we continue to attract from researchers around the world.This issue showcases five diverse and timely contributions that reflect the broad aims and scope of the journal. Each article addresses contemporary challenges and proposes informed perspectives grounded in empirical evidence or theoretical innovation. Below, we offer a brief overview of each contribution:• Wasatiyah Optimization in Sustainable Wealth ManagementAuthor: Prof. Dr. Tariqullah KhanIn this compelling paper, Prof. Khan introduces a novel framework for Islamic Wealth Management based on the principle of Wasatiyah (moderation). He presents the concept of Normalized Balance Coordinates (NBCs) as a multidimensional performance metric that balances ethical, environmental, and economic considerations. The paper provides practical strategies through the STO (Substitutions, Transformations, Offsets) model and challenges the paradigm of wealth maximization, proposing instead a holistic, values-driven approach to financial sustainability. This contribution represents an important theoretical and practical advancement in Islamic economics and finance.• Total Factor Productivity and Foreign Human Capital – Evidence from the Western BalkansAuthors: Daria Hukic and Faruk HadzicThis empirical study investigates the relationship between foreign human capital and innovation in the Western Balkans, with a focus on Total Factor Productivity as a measure of innovation. Employing instrumental variable techniques to control for endogeneity, the authors provide nuanced insights into how diaspora and immigration patterns influence productivity across sectors. Their findings are especially valuable for policymakers striving to bridge human capital gaps and leverage migration as a catalyst for development in transitional economies.• Profitability and Resilience: Comparative Analysis of the Performance of Islamic and Conventional Insurance Companies in the GCC RegionAuthor: Abdulrahim AmrullahAgainst the backdrop of a rapidly growing global Takaful industry, this paper offers a rigorous comparative analysis of Islamic and conventional insurance firms in the Gulf Cooperation Council (GCC) region. Utilizing a decade of panel data and SGMM estimation, the author identifies key performance differences, revealing that while Takaful firms generally operate with lower capitalization and solvency, they exhibit stronger premium growth. This work not only deepens our understanding of the region’s insurance landscape but also highlights the sector’s adaptability in the face of macroeconomic challenges, including COVID-19.• Structuring Islamic Financial Literacy Construct to Measure Islamic Banking Products Adoption in Uganda: Content Validation of the Survey InstrumentAuthors: Yusuf Kaweesa and Romzie RosmanWith Islamic banking still in its infancy in Uganda, this study contributes to foundational knowledge by developing and validating a survey instrument to measure Islamic financial literacy. Using a structured five-stage validation process and expert panels, the authors establish content validity for a tool that will be crucial in understanding adoption trends of Islamic financial products in emerging markets. The study lays the groundwork for future empirical work and highlights the importance of localized, context-specific measures in Islamic finance research.• Crowdfunding: The End of an Era or a Course Correction? A Bibliometric AnalysisAuthor: Shadi Al ShebliIn this bibliometric investigation, the author examines the lifecycle of crowdfunding research, tracing its rise from 2010 and the notable decline since 2020. Utilizing co-authorship and citation network analyses within a Kuhnian theoretical framework, the study identifies three distinct research phases and suggests that the decline may signal a paradigm shift rather than a loss of interest. The paper also advocates for greater use of network science to enhance future bibliometric studies. This is a significant contribution for researchers and editors tracking scholarly trends and intellectual evolution within financial innovation.Together, the articles in this issue reflect the broad vision of JELS—to bridge disciplines, regions, and methodological approaches in the pursuit of knowledge that addresses real-world challenges. We are deeply grateful to all contributing authors for entrusting us with their work and to our anonymous reviewers, whose insightful and constructive feedback helped refine and strengthen each submission. Their expertise and dedication remain critical to maintaining the academic standards of this journal.As Editor-in-Chief, I take this opportunity to thank all authors for choosing JELS as the platform for disseminating their important work. We also extend our deepest appreciation to our dedicated peer reviewers, whose valuable and constructive feedback ensured the academic rigor and integrity of each published paper. Your commitment is vital to the success and credibility of this journal.We encourage researchers and scholars from all relevant disciplines to consider submitting their original research, reviews, and case studies for the second issue of Volume 2, scheduled for publication at the end of this year. As we continue to improve and build our international reputation, your contributions play a central role in shaping the academic dialogue that JELS strives to foster.We remain committed to our mission and look forward to continued collaboration with the global scholarly community.Sincerely, Edib SmoloThe Co-Founder & Editor-in-ChiefJournal of Economics, Law & Society (JELS)